Angiotropic intravascular large-cell lymphoma with massive cerebral extension. Issue 8 (August 1993) - Torenbeek, R; Scheltens, P; Strack van Schijindel, R J; Algra, P R; Heimans, J J; van der Valk, P
Abstract : Angiotropic intravascular large-cell lymphoma (AILL) is a rare, generally fatal disease characterised by a multifocal proliferation of neoplastic mononuclear cells within small blood vessels. The diagnosis of a patient was made at necropsy. The malignant cells had infiltrated the periventricular areas of the brain.